Some New Approaches to the Development Creativity in Classroom - Sekulić-Majurec, Ankica (Array, 2002)
The most of professional papers about teaching as well as the most of school regulations, particularly those including classroom teaching, stresses the importance of the students' creativity development. This development of their creativity is generally seen as one of the crucial tasks of the teaching process in the classroom. However, the question is how much it has been realised in our schools, and how much it is possible to realise, regarding some of its key features. This is the issue this paper discusses. To answer this question, it is necessary to explain the phenomenon of creativity in more details, and especially those parts of this phenomenon which are more related to classroom teaching. Only then it is possoble to examine which features of our school and classroom teaching enable and which ones limit the development of students' creativity. This paper shows that our schools, and particularly the teaching process itself, are not appropriate enough to realise this important task - to develop the creativity of students.